The Meaning and Uses of Βασιλεία in the Gospel of Matthew : Semantic Monosemy and Pragmatic Modulation - Ålöw, Tobias, (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2024., 2024)
Contrary to the prevailing view that Î²Î±ÏƒÎ¹Î»ÎµÎ¹ÌÎ± is a verbal noun signifying God's rule, this study demonstrates how the term's pragmatic range in Matthew's Gospel covers both five distinct types of use and their integration into a coherent concept. The study, which is the first to examine all occurrences of Î²Î±ÏƒÎ¹Î»ÎµÎ¯Î± in the First Gospel from the perspective of semantic monosemy, extends and enhances our appreciation of the Matthean Zentralbegriff , and engenders a more accurate apprehension of the nature and aims of the Matthean narrative and the theological views it conveys.